Central Oxytocin and Food Intake: Focus on Macronutrient-Driven Reward - Klockars, Anica; Levine, Allen Stuart; Olszewski, Pawel Karol (Frontiers in Endocrinology, 2015)
Centrally acting oxytocin (OT) is known to terminate food consumption in response to excessive stomach distension, increase in salt loading and presence of toxins. Hypothalamic-hindbrain OT pathways facilitate these aspects of OT-induced hypophagia. However, recent discoveries have implicated OT in modifications of feeding via reward circuits: OT has been found to differentially affect consumption of individual macronutrients in choice and no-choice paradigms. In this mini-review, we focus on presenting and interpreting evidence that defines OT as a key component of mechanisms that reduce eating for pleasure and shape macronutrient preferences. We also provide remarks on challenges in integrating the knowledge on physiological and pathophysiological states in which both OT activity and macronutrient preferences are affected.